2009
DOI: 10.1002/jps.21765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Route of Administration of Human Recombinant Factor VIII on Its Immunogenicity in Hemophilia A Mice

Abstract: Factor VIII is a multi-domain glycoprotein and is an essential cofactor in the blood coagulation cascade. Its deficiency or dysfunction causes Hemophilia A, a bleeding disorder. Replacement using exogenous recombinant Factor VIII (FVIII) is the first line of therapy for Hemophilia A. Immunogenicity, the development of binding (total) and neutralizing (inhibitory) antibody against administered protein is a clinical complication of the therapy. There are several product related factors such as presence of aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 13 publications
2
23
0
1
Order By: Relevance
“…There are several examples from preclinical relative immunogenicity studies that show the sc route is more immunogenic than the iv route. The sc administration of FVIII showed significantly higher total antibody titers compared to hemophilia A mice that were given FVIII via the iv route (12). A similar observation has been made for other therapeutic proteins such as interferon alpha and human growth hormone (3,13,14).…”
Section: Immunogenicity Of Proteins Given Via Sc Routesupporting
confidence: 60%
“…There are several examples from preclinical relative immunogenicity studies that show the sc route is more immunogenic than the iv route. The sc administration of FVIII showed significantly higher total antibody titers compared to hemophilia A mice that were given FVIII via the iv route (12). A similar observation has been made for other therapeutic proteins such as interferon alpha and human growth hormone (3,13,14).…”
Section: Immunogenicity Of Proteins Given Via Sc Routesupporting
confidence: 60%
“…Several reports have indicated that the intravenous application route for proteins is associated with a less immunogenic response than the subcutaneous or intramuscular application routes. 40,41 Therefore, we expected to see a higher incidence of antibodies against FVIII after subcutaneous application if mice were able to respond to FVIII. Our data confirmed this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were sacrificed at week 6 and plasma was collected. Total anti‐FVIII titers were determined using an ELISA as previously described . Inhibitory anti‐FVIII titers were quantified with the Bethesda assay.…”
Section: Methodsmentioning
confidence: 99%